2019
DOI: 10.1093/jbcr/irz084
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Clinical Trial Recruitment and Retention Challenges in the Burn Population: Lessons Learned From a Trial Examining a Novel Intervention for Chronic Neuropathic Symptoms

Abstract: Long-term trials are key to understanding chronic symptoms such as pain and itch. However, challenges such as high attrition rates and poor recruitment are common when conducting research. The aim of this work was to explore these issues within a long-term randomized control trial using transcranial direct current stimulation to treat pain and itch. This parallel double blinded, placebo-controlled randomized trial was comprised of 15 transcranial direct current stimulation visits and 7 follow-up visits. Partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Recently, thanks to the development of computer FEM models and more complex tDCS devices allowing up to 32 stimulating electrodes, high-density tDCS [32] and network-based tDCS [33] protocols have been tested with promising results compared to conventional montages. The development of home-based devices is assumed to be determinant for the clinical translation of tDCS as it overcomes the issue of patients' travel to a research institution or hospital and therefore, high rate of drop-outs [34,35]. Increase in current intensity thought to induce strong neuroplastic effects has also been tested without causing any significant side effects [36].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, thanks to the development of computer FEM models and more complex tDCS devices allowing up to 32 stimulating electrodes, high-density tDCS [32] and network-based tDCS [33] protocols have been tested with promising results compared to conventional montages. The development of home-based devices is assumed to be determinant for the clinical translation of tDCS as it overcomes the issue of patients' travel to a research institution or hospital and therefore, high rate of drop-outs [34,35]. Increase in current intensity thought to induce strong neuroplastic effects has also been tested without causing any significant side effects [36].…”
Section: Introductionmentioning
confidence: 99%
“…However, current literature on NIBS in burn for treating these and other associated symptoms remains limited and future trials are merited to investigate the efficacy of this approach. Specifically, home-based supervised devices may be utilized in order to limit attrition rates as observed in previous trials [127]. Our review of the neural circuitry involved in post burn symptoms and suggested targeted areas for stimulation provides a spring board for future study initiatives.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, some studies have utilized home-based tDCS devices with promising results and, most importantly, with no side-effects [123À125]. Thus, home-based supervised sessions, as recommended by Charvet and colleagues [126], could be an alternative to facilitate tDCS and tACS implementation and reduce attrition rates as often observed in clinical trials of long duration [127], as well as to promote long-lasting tES-related effects. Besides the number of sessions, the intensity of stimulation is another parameter to take into account.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting this finding, another study found that around 36% of withdraws were related to protocol issues as the duration of the study, length of procedures, and other 33% were related to inconvenience as taking time out of work and distance [ 52 ]. In fact, as shown in other stimulation sessions, the number of sessions seems to be related to the dropout rate [ 53 ]. However, the use of online visits might improve this recruitment and the adherence rate [ 54 ].…”
Section: Discussionmentioning
confidence: 96%